The Impact of Dollarization Policy on Zimbabwe Exports: A Gravity Model Approach - Tomu, Lilian; Mutodi, Knowledge; Chuchu, Tinashe; Maziriri, Eugine Tafadzwa (International Journal of Economics and Financial Issues, 2021)
This paper investigates the impact of dollarization policy on Zimbabwe exports over a period of 20 years. The study used panel data for 50 Zimbabwe potential historical trading partners. Random Effects Model (REM) was applied to estimate the gravity model equation. Panel Feasible Generalized Least Squares (FGLS) regression technique corrected for heteroskedasticity and contemporaneous correlation across panels was applied to probe factors that drive Zimbabwe export flows. The results provide insights on the impact of dollarization policy, GDP, bilateral exchange rate, SADC membership status and population on Zimbabwe exports. If monetary authorities involuntarily re-dollarize the economy owing to monetary autonomy erosion, emphasis should be directed towards internal devaluation which could be attained by measures intended to exert downward pressure on domestic costs, wages and prices to recuperate export competitiveness. Further, government has to create an environment that encourage foreign direct investment inflows to ease liquidity challenges probable to be experienced under dollarization regime. Nevertheless, macroeconomic fundamentals ought to be addressed with action to spur economic growth. Sufficient resources should be channelled towards increasing the country's productive capacity, and this can enhance country‘s ability to supply export products to the international market, and curb import growth. Keywords: Dollarization policy, gravity model, Zimbabwe JEL Classifications: F60, F63, 63 DOI: https://doi.org/10.32479/ijefi.11315